Video streaming over wireless LAN using scalable extension of H.264/AVC - Maarif, Haris Al Qodri; Gunawan, Teddy Surya (2008)
The scalable video coding extension of H.264/AVC is a current standardization project. This paper deals with encoding process of the Fine-Grain SNR Scalability (FGS) scheme with two enhancement layers for enhancing the streaming video quality over wireless LAN. The scalable video coding algorithm has been implemented and simulated with various parameters in various wireless LAN conditions. The simulation results showed that the proposed algorithm is suitable for wireless LAN channel capacity.